Professionalism in the office : proven techniques for administrators, secretaries, and coordinators - Manning, Marilyn (Crisp Pub. Menlo ParkUS, 2001)
Advises on aspects of professional behaviour and performance including: personal appearance; non-verbal communication; establishing priorities; time-management. Lists skills needed in areas including project management and decision making. Includes practical communication tips for writing (including Emails); listening; planning and facilitating meetings; and making presentations. Suggests techniques for developing strong working relationships that include a 6-step plan for resolving conflict; and 8 tips for establishing good worker-manager rapport.\n